Classification of Emotions in Song Lyrics in the Album Markers and Such Pens Flashdisk by Sal Priadi: A Study of Literary Psychology - Rahmatillah; Juni Ahyar; Rasyimah (Global Action and Education for Society, 2026)
This study aims to classify the various forms of emotion found in the songs on Sal Priadi's album Markers and Such Pens Flashdisk based on David Krech's literary psychology theory, which classifies emotions into four categories: basic emotions, emotions related to sensory stimuli, and emotions related to others. This study employed qualitative research with descriptive analysis methods. The data sources were the songs on Sal Priadi's album Markers and Such Pens Flashdisk. The data collection techniques used were recording, listening, and note-taking. The results of the study suggest that the songs in Sal Priadi's album Markers and Such Pens Flahsidsk contain various forms of emotion which are analyzed based on David Krech's literary psychology theory. The most common emotions were basic emotions. The song on Sal Priadi's album Markers and Such Pens Flashdisk with the most emotional content was Gala Bunga Matahari.